The impact of hiring directors' choice‐supportive bias and escalation of commitment on CEO compensation and dismissal following poor performance: A multimethod study - Zorn, Michelle L.; DeGhetto, Kaitlyn; Ketchen, David J.; Combs, James G. (Strategic Management Journal, 2020)
Abstract Research Summary Boards of directors make high‐stake decisions that involve hiring, compensating, and dismissing CEOs. Building on theory about choice‐supportive bias and escalation of commitment, we theorize that “hiring directors” (directors who were present during a CEO's hiring) will display choice‐supportive bias and escalate commitment to poorly performing CEOs. Primary data from 73 directors indicate that directors are indeed biased toward CEOs they help hire. Archival data from S&P 1500 firms reveal that, following poor performance, the number of hiring directors is positively related to the increase in CEO pay and lower likelihood of CEO dismissal. Building on theory about board experience, we also predict and find that more experienced boards reduce the tendency to escalate. Thus, bias among hiring directors can be mitigated via experience. Managerial Summary Making a choice such as casting a vote or selecting a restaurant leads people to view their selection favorably even if evidence emerges suggesting it was a bad choice. We examine whether corporate directors fall prey to this choice‐supportive bias when involved in CEO hiring. We found that directors who are part of the hiring process tend to have an overly rosy view of the person selected. Moreover, if the firm is performing poorly, a board with more directors who helped hire the current CEO will tend to increase the CEO's pay more and are less likely to fire the CEO than a board with fewer such directors. This problem is reduced if the board has highly experienced directors among its ranks.